2018
DOI: 10.1111/bph.14124
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to valproic acid affects the histaminergic system and the social behaviour of adult zebrafish (Danio rerio)

Abstract: VPA exposure in early development causes molecular and neurochemical alterations in zebrafish, which persist into adulthood and accompany impaired sociability. These findings will highlight the possible involvement of the histaminergic system in outcomes related to neuropsychiatric disorders. Furthermore, it supports zebrafish as a tool to investigate mechanisms underlying these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 63 publications
(83 reference statements)
5
58
0
Order By: Relevance
“…In addition to several reports on the effect of VPA on the serotonergic system, studies on zebrafish have shown that VPA treatment also affects key genes in other monoaminergic systems, in particular dopamine [ 19 ]. We thus analyzed genes involved in dopamine synthesis and metabolism in zebrafish larvae from the two different strains treated with our administration regimens (1 µM VPA for 24 or 48 h).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to several reports on the effect of VPA on the serotonergic system, studies on zebrafish have shown that VPA treatment also affects key genes in other monoaminergic systems, in particular dopamine [ 19 ]. We thus analyzed genes involved in dopamine synthesis and metabolism in zebrafish larvae from the two different strains treated with our administration regimens (1 µM VPA for 24 or 48 h).…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy among our study and previous studies that did not report neurotoxic effect of VPA at higher concentrations, may be explained by the genetic differences of the inbred strains used in the studies. Zimmermann et al [ 15 ] did not report the strain of the animals used in their study, while Baronio et al [ 19 ] used the Turku strain. This study reported a high mortality rate (above 50%) in larvae treated with 50 µM, a high level of deformities and arrested development using 35 µM VPA, while no significant effects on mortality were reported by 25 µM VPA treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the old-generation H3R antagonist ciproxifan attenuates at least some sociability deficits and stereotypies present in the animal model of autism induced by valproic acid (VPA) 1 . Notably, embryonic exposure to VPA causes several molecular and neurochemical changes in zebrafish, which continue into adulthood and accompany impaired sociability, demonstrating the possible association between brain histaminergic system and the outcomes related to neuropsychiatric disorders 20 . In the postmortem dorsolateral prefrontal cortex of 13 human subjects with ASD, significant alterations in the expression of key histamine genes, including all HR subtypes H1-4Rs, have been observed, signifying the involvement of modulated histaminergic signaling in the brain of ASD subjects 21 .…”
Section: Introductionmentioning
confidence: 99%